[tex]\Large\blue{\tt{\:\:COMPLEMENTARY\: ANGLES}}[/tex]
[tex]\large\bold{\tt{Statement:}}[/tex] ∠1 is complementary to ∠2.
[tex]\large\bold{\tt{Given:}}[/tex] m∠1 = 2m∠2
[tex]\large\bold{\tt{Solve\:for:}}[/tex] m∠1
[tex]\large\bold{\tt{Solution:}}[/tex]
First, find m∠2
[tex] \\ \large \tt \: m∠1 + m∠2 = 90° \\ \\ \large \tt (2m∠2) + m∠2 = 90° \\ \\ \large \tt 3m∠2 = 90° \\ \\ \large \tt \frac{3m∠2}{3} = \frac{90°}{3} \\ \\ \large \tt m∠2 = 30°[/tex]
Then, substitute the m∠2 to find the m∠1
[tex] \large \tt m∠1 + m∠2 = 90° \\ \\ \large \tt m∠1 + 30° = 90° \\ \\ \large \tt m∠1 = 90° - 30° \\ \\ \large \red{ \boxed{ \tt {m∠1 = 60°}}}[/tex]